Addressing math anxiety in the classroom. (March 2014) - Finlayson, Maureen
In today's educational systems, students of all levels of education experience math anxiety. Furthermore, math anxiety is frequently linked to poor achievement in mathematics. The purpose of this study is to examine the causes of math anxiety and to explore strategies which pre-service teachers have identified to overcome math anxiety. The methodology included conducting surveys with 70 pre-service teachers in Canada and completing a critical analysis of the data to provide an overview of the causes of math anxiety. These data indicate that pre-service teachers have encountered math anxiety in many situations. These causes include: lack of self-confidence, fear of failure; teaching styles; ineffective learning practices, and non-engagement of students. Furthermore, these data indicate that facing math anxiety have empowered the participants to devise strategies which have enabled them to overcome math anxiety. The author suggests that an improved understanding of math anxiety hold implications for all students and educators of mathematics.